DAMPAK KUALITAS PRODUK, HARGA DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN SAYURAN HIDROPONIK - Asyari, Muhammad ali Hasim; Risnawati, Risnawati; Jufri, Fikri; Asman, Asman (Institute of Computer Science (IOCS), 2024)
One of the strategy to increase people's interest in choosing to consume hydroponic vegetables is to provide a sense of satisfaction to consumers. Good product quality, affordable prices, and excellent service can all contribute to customer satisfaction with hydroponic vegetables. The purpose of this study is to investigate the ways in which Paser Hydroponics' customer satisfaction can be significantly impacted by factors such as product quality, price, and service. This sort of exploration is quantitative elucidating investigation and utilizations the Unintentional Testing inspecting procedure. This study used primary data with a lemeshow formula (for an unknown population) sample size of 97 individuals. In this study, multiple linear regression analysis was used as the method of analysis. The study's results show that the coefficient of determination (R2) is 0.623 (62.3%), it shows that there is a relationship between each independent variable. The results of simultaneous regression analysis or F-test show that product quality, price and service significantly influence consumer satisfaction, while partial or T-test shows that the price variable is not significant on consumer satisfaction.